Organic carbon in Rhizophora and Avicennia mangrove litter of South Kalimantan, Indonesia - PUTRI MUDHLIKA LESTARINA; DIETRIECH GEOFFREY BENGEN; TRI PRARTONO; MUHAMMAD AHSIN RIFA'I; NEVIATY PUTRI ZAMANI; SELVIANI SELVIANI (Society for Indonesian Biodiversity, 2026)
Abstract. Lestarina PM, Bengen DG, Prartono T, Rifa'i MA, Zamani NP, Selviani. 2026. Organic carbon in Rhizophora and Avicennia mangrove litter of South Kalimantan, Indonesia. Biodiversitas 27 (1): d270132. https://doi.org/10.13057/biodiv/d270132. Mangrove ecosystems serve as major blue carbon sinks due to their high productivity and slow decomposition under anaerobic conditions. This study examined organ and species-level variations in the organic carbon content of Rhizophora mucronata and Avicennia marina at two coastal sites in South Kalimantan, Indonesia-Kintap and Asam-Asam. Samples of stems, twigs, leaves, roots, and flowers were analyzed using the Walkley-Black method. The average organic carbon content of R. mucronata was 7.603%, while that of A. marina was 6.193%. The highest carbon concentration occurred in stems and twigs, followed by roots, leaves, and flowers. Mean carbon content was slightly higher in Kintap (7.091%) than in Asam-Asam (6.704%), though the difference was not statistically significant. Regression analysis indicated that plant organs significantly influenced organic carbon levels (p = 0.004), whereas location, station, and species did not. These findings emphasize that organ-specific characteristics-particularly lignin-rich woody tissues-are key determinants of carbon retention in mangroves. Incorporating such organ-level variability enhances the accuracy of blue carbon estimates and supports ecosystem-based conservation and climate mitigation strategies. Moreover, these findings highlight the ecological significance of organ-specific carbon storage in dominant mangrove species, reinforcing their role in sustaining ecosystem diversity and supporting blue carbon conservation strategies under global climate change agendas.